Comparative pharmakognostical study of roots of Rosa Majalis Herrm. and Rosa Canina L. - Oproshanska, Tetiana; Khvorost, Olga; Skrebtsova, Kateryna; Vitkevicius, Konradas (ScienceRise: Pharmaceutical Science, 2021)
The aim is to conduct a comparative pharmacognostical study of the series of roots of Rosa (R.) majalis Herrm. and Rosa (R.) canina L. with the establishment of diagnostic features of morphological and anatomical structure and boundary limits of numerical indicators of raw materials. Materials and methods. The fresh and dry raw materials were used to study the macroscopic microscopic features by microscope Delta optical BioLight 300 (Poland). Determination of total polyphenols was performed by spectrophotometry (on a spectrophotometer Optizen POP (Korea)) and HPLC (chromatograph an Agilent 1200 3 D LC System Technologies (USA)). Results. The morphological (nature of the surface (periderm) and fracture) and anatomical (color of cell walls and their cavities; location of the sclerenchyma; the presence of a crystalline coating of the sclerenchyma at the root of R. canina; of various elements of the remains of the tetraarchic conducting bundle in the center of the root) diagnostical features of roots of R. majalis and R. Canina were established. Comparing the numerical values of loss on drying (not more than 10 %), total ash (not more than 5 %), extractable matter (not less than 9 %) and the quantitative content of total polyphenols (not less than 4 %) it was determined that both types of raw materials according to these indicators are almost indistinguishable. Conclusions. Loss on drying, total ash, extractable matter and content of total polyphenols of the root of R. majalis and R. canina do not have significant differences, that is why the root of both plant species can be used as medicinal plant raw materials such as “Rose root”. The obtained data will be used in further research when creating methods of quality control of plant raw materials and phytomedicines